Ultraviolet Assisted Autolysis Of Sea Cucumber (Stichopus Horrens) Body Wall For The Enhancement Of Sulfated Polysaccharides Release - Umam, Nada Itorul (2023)
Sea cucumbers (Stichopus horrens) contain important bioactive compounds called sulfated polysaccharides (SP), which can be extracted by autolysis process utilizing its endogenous enzyme. However, this process is slow and not efficient. The aim of this study was to evaluate the mechanism of UV assisted autolysis in enhancing the release of SP from sea cucumber body wall. In phase I, the effects of UV dosage and pH on endogenous proteases activity, biochemical, and structural changes of SHBW during autolysis were evaluated. Frozen SHBW was homogenized with and without buffer (pH 6, 7, 8) and exposed to low (10,800 J/m2) and high (324,000 J/m2) UV dosage prior to autolysis at 50 °C for 4 and 8 hours. The endogenous protease activity and respective biochemical changes were evaluated from the soluble fraction while the insoluble fraction of SHBW was evaluated for secondary protein structural changes and thermal stability using Fourier-transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Thermogravimetry Analysis (TGA). Increase in UV dosage by 30x, increased proteolytic activity by 4.5-fold after 4 hours autolysis, resulting in increased soluble protein, hydroxyproline, and glycosaminoglycan (GAG) content by 5, 4, and 3 folds, respectively. Although sample without buffer showed similar endogenous protease activity with control sample, the total soluble protein, hydroxyproline, and GAG were higher by 4, 0.1, and 2.5 folds, respectively.